Do fado de padaria ao rap do carro zero: evolução e indefinição da música nos jingles publicitários - Santos Júnior, Alaor Ignácio dos (2016)
There are two different symbols to compose jingles: music and verbal language. Musical practice alludes to the art of organizing tone, as in the aspect adopted by advertising, using common standards to a favourable reception to a certain target audience, starting with texts and a music-socio-cultural context preexistent in the listener´s repertoire that, lato senso, may be defined in musical genders. These advertising languages, defined as a persuasion element and denominated jingles, in its composing form, results in a redundant media transmission and a continuous reception by a role model listener that assimilates, if not while persuaded, as reproducer and repeater of its commonly simplified lyrics and melodies. Measure such reflexes in the receptor memories was one of the aspects aimed in the study (LOTMAN, 1996), beginning with the re-elaboration of what is observed in the cultural dynamics (FERREIRA, 2004) not as a “bunch of information” but as an organized and complex mechanism that recodifies and translates the messages from “the other symbol”. Also, an eventual musical gender hybridizes as a counterpoint to the existence of a certain “purism” or musical gender hegemony that composes the jingles, with regard to rhythms, instrumentation, structure and contextualization in different period of times were analyzed in this study. It is here proposed an hybrid and mediated jingle (BARBERO, 2009), either by the musical melting pot in its compositions or by the dialogical frontier with the new medias, constantly transposing supports, receiving and surviving through the years or even decades with an updated and critical reading as an advertising piece guided not only to electronic media but also the virtual ones, in the different context and relation with contemporaneous music and technology